Snow resources of Krasnaya Polyana area (Western Caucasus) - A. D. Oleynikov (Лëд и снег, 2015)
The paper deals with study of snowiness and estimation of modern tendencies of its changes in the area of Krasnaya Polyana in the West Caucasus. Olympic Games will take place here in February, 2014. The paper is based on the data of meteorological stations Krasnaya Polyana (567 m), Achishho (1880 m) and snow surveys along the Mzymta River valley (0–2500 m). Period under study characterized by winters with different snowiness. This difference is analyzed due to their changes in altitude levels. During two last decades, the noticeable reduction of snowiness occurred in the investigated district. The dependence between snowy winters and periods of cold temperatures is identified. In seasons of anomaly high and low snowiness the difference of snow depth can reach 5 m (Achishho). In places of Olympic ski lower stations (Gornaya Karussel, Gasprom, Rosa-Hutor) the temperature of cold period runs from −1,6 ºC up to 4,9 ºC, and the periodicity of winters with positive temperatures is 86% on this level. Parameters of winter conditions are given in the paper, and we can consider them as a paradox of Krasnaya Polyana winters